Legal Force of Electronic Signatures as a Valid Evidence in Authentic Deeds - Sterisa, Raden Roro Nadia; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. The Legal Power of Electronic Signatures as Valid Proof of Authentic Deeds, becomes a problem because the Notary Law has not explicitly regulated the authority of notaries in using electronic signatures for authentic deeds, although the Electronic Transactions and Information Law has recognized the validity of electronic signatures. This study aims to analyze: 1) the legal power of electronic signatures as valid proof of authentic deeds according to the Notary Law and the Electronic Transactions and Information Law 2) the resolution of normative conflicts regarding the legal power of electronic signatures as valid proof of authentic deeds between the provisions of the Notary Law and the Electronic Transactions and Information Law. The approach method in this study is the statute approach. This type of research is normative research. The types and sources of data in this study are secondary data obtained through literature studies. The analysis in this study is prescriptive.The results of the study show that the Legal Power of Electronic Signatures as Valid Proof of Authentic Deeds According to the Notary Law and the Electronic Transactions and Information Law, in making authentic deeds still requires wet signatures and the physical presence of the parties before the notary, based on the explanation of Article 15 paragraph (3) of the Notary Law is not in line with Article 16 paragraph (1) letters m and c of the Notary Law. Article 16 paragraph (1) letters m and c concerning the authority of the notary in paragraph (1) can cause problems regarding the authenticity of the deed in the application of electronic signatures. Therefore, the use of electronic signatures on partij and relaas deeds still does not have its validity. The resolution of the conflict of norms regarding the legal force of electronic signatures as a valid evidentiary force in authentic deeds between the provisions of the Notary Law and the Electronic Transactions and Information Law requires a comprehensive approach so that the use of electronic signatures in making authentic deeds can be widely accepted and provide legal certainty for all parties involved by prioritizing the principle of lex specialis, and carrying out conformity between the Notary Law and the Electronic Transactions and Information Law.Keywords: Legal Power, Signature, Authentic Deed.